Human Plasma ATP Concentration - Gorman, Mark W; Feigl, Eric O; Buffington, Charles W (Clinical chemistry (Baltimore, Md.), 2007)
Background: Human plasma ATP concentration is reported in many studies as roughly 1000 nmol/L. The present study tested the hypothesis that the measured plasma ATP concentration is lower if ATP release from formed blood elements is inhibited during blood sample processing. A second hypothesis was that pretreatment with aspirin to inhibit platelets would reduce the measured plasma concentration of ATP. Methods: Blood was sampled from the antecubital vein in 20 healthy individuals 30 and 60 min after ingestion of aspirin (325 mg) or placebo. Aliquots of each blood sample were added to the usual EDTA/saline solution to inhibit ATP catabolism, or to a new stabilizing solution designed to both stop ATP catabolism and inhibit ATP release from blood elements. The stabilizing solution contained NaCl, EDTA, tricine buffer, KCl, nitrobenzylthioinosine, forskolin, and isobutylmethylxanthine. Plasma ATP was measured with the luciferin–luciferase assay with standard additions in each sample to determine ATP content. Hemoglobin concentration was used as an index of sample hemolysis, and the plasma ATP concentration was corrected for the hemolysis component. Results: Aspirin pretreatment had no effect on plasma ATP concentrations. However, use of the stabilizing solution resulted in mean (SD) ATP concentrations 8-fold lower than the use of EDTA alone [28 (16) vs 236 (201) nmol/L; P <0.001]. Conclusion: When precautions are taken to inhibit ATP release from blood elements during sample preparation, human venous plasma ATP concentration is much lower than previously reported.